Denver wetlands: wet & wild in the city - Smith, Pam, author; Kuhn, Bernadette, author; Holfelder, Kirstin, author; Colorado Natural Heritage Program, publisher (Colorado State University. Libraries, 2015)
Brochure provides information about urban wetlands in Denver including Parkfield Lake Natural Area, Westerly Creek and Bear Creek Park.
Denver County Critical Urban Wetlands Brochure
Authors from CNHP website.
Brochure was produced by the Colorado Natural Heritage Program in collaboration with the Environmental Protection Agency, and the City and County of Denver.
Keywords: wetlands; recreation; water quality; wildlife; flood control